Angiofollicular lymph node hyperplasia (Castleman). Issue 4 (April 1972) - Anagnostou, Dimitra; Harrison, C. V.
Abstract : Six personally observed cases of this lesion are reported and the literature is reviewed. One hundred and thirty-four cases have been reported to date. The lesion has occurred in many sites, but is commonest in the thorax (60%), abdomen (11%), neck (14%), and axilla (4%). Ninety per cent of cases are symptomless or have only the pressure symptoms, 10% have systemic signs, namely, fever, raised ESR, anaemia, cured by removal of the tumour. These cases have a slightly different histology. All recorded cases have been benign. Microscopically the lesion is follicular but instead of germinal centres the follicles have one or more thick-walled arteries and often some surrounding histiocytes. Increased numbers of vessels occur between the follicles, whilst sinuses are absent. These vessels have thick, cellular walls like post-capillary venules. Sometimes they become hyaline. The cases with symptoms have true reaction centres as well as a few intrafollicular vessels. Between the follicles there are increased numbers of vessels and, in addition, there may be collections of plasma cells or eosinophils.